Portable and quantitative detection of carbendazim based on the readout of a thermometer. (30th July 2021) - Fu, Ruijie; Zhou, Jing; Liu, Yanlin; Wang, Yiwen; Liu, Haoran; Pang, Junxiao; Cui, Yongliang; Zhao, Qiyang; Wang, Chengqiu; Li, Zhixia; Jiao, Bining; He, Yue
Highlights: A portable and cost-effective method for the detection of carbendazim was designed. Gold nanoparticles with strong photothermal effect under laser irradiation were utilized as indicators. A thermometer was employed to record the detection signal. A detection limit of 17.22 ng/mL was obtained. Excellent sensing performance for the detection of carbendazim in citrus fruit and cabbage samples was achieved. Abstract: The detection of carbendazim (CBZ) is important for food safety and human health. However, most current analytical methods require large instruments and highly trained operators. In order to solve this problem, herein, an innovative portable and quantitative photothermal assay platform relying on a thermometer readout for the detection of CBZ has been developed. Gold nanoparticles (AuNPs), which exhibit a strong distance-dependent photothermal effect under specific laser irradiation, were utilized as indicators. The CBZ aptamer was introduced to protect AuNPs from salt-mediated aggregation. When CBZ is present, the binding event between CBZ and aptamer leads to the loss of the aptamer protective effect on AuNPs, and AuNP aggregation occurs. Under 650-nm laser irradiation, the increase in temperature associated with an AuNP-dependent photothermal effect is highly related to the CBZ concentration. Having the advantages of user-friendliness, low cost, quick response, and portability, this method has great potential for on-site applications.